Relationship between quadriceps muscle architecture and lower limb strength and physical function in older adults community-dwelling individuals: a cross-sectional study - Cinarli, Fahri Safa; Ulubaba, Hilal Er; Ucar, Ozan; Kilinc, Deniz Can; Ciftci, Rukiye; Karayigit, Raci; Aldhahi, Monira I; Al-Mhanna, Sameer Badri; Gülü, Mehmet (Frontiers in Public Health, 2024)
Factors related to muscle architecture may lead to functional limitations in activities of daily living in the elderly. The aim of this study was to investigate the relationship between quadriceps femoris (QF) architecture and physical function in elderly community-dwelling people. Methods: The study encompassed 25 community-dwelling elderly participants, aged over 65 (comprising 14 males and 11 females), who were not engaged in regular physical activity.The rectus femoris (RF) and vastus intermedius (VI) muscle thickness as well as RF cross-sectional area (CSA) were assessed by the 2D ultrasonography. The 30 Seconds Chair Stand Test (30sCST) and the Timed Up and Go Test (TUG) were used to assess lower body muscle power and functional mobility, respectively. Results: The QF muscle architecture showed moderate and large correlation with 30sCST (r range = 0.45-0.67, p < 0.05) and TUG (r range = 0.480 - 0.60, p < 0.05). RF thickness was a significant (p < 0.01) independent predictor of 30sCST (R2 = 0.45) and TUG (R2 = 0.36). VI thickness was a significant (p < 0.05) independent predictor of 30sCST (R2 = 0.20) and TUG (R2 = 0.231). RF CSA was a significant independent predictor of 30sCST (R2 = 0.250, p < 0.05) and TUG (R2 = 0.27, p < 0.01). Multiple linear regression models explained 38% of the 30sCST variance and 30% of the TUG variance in the elderly. Conclusion: The quadriceps muscle group directly affects basic activities of daily living in the elderly. Ultrasound measurements, which are a noninvasive tool, are extremely valuable in understanding the limitation of activities of daily living in the elderly.